The Efforts of Islamic Religious Education Teachers in Developing Students' Characteristics in The Almarjan Duta Indah Integrated Islamic Elementary School, Bekasi City - Ansori, Dedi; Haryono, Pauzan; Arifin, Zaenal (Proceeding International Conference on Education, 2023)
The efforts of Islamic Religious Education teachers in fostering student morals have an important urgency in forming good character. The purpose of this study was to find out the concepts used by teachers in providing Islamic Religious Education to SDIT Almarjan Duta Indah Bekasi students. The research method is a qualitative method with a descriptive approach. Data collection techniques used in this study included class observation, teacher interviews, and document study. The subjects in this study were students of SDIT AlMarjan, Bekasi City. The results of the study show that the efforts of Islamic Religious Education teachers in fostering student morals have positively impacted student character development. Teaching practices that involve interactive learning, the use of role models, and the use of religious values in the context of everyday life help students understand and internalize moral and ethical values. Thus, the implications of the efforts of Islamic Religious Education teachers in fostering student morals are very important in improving student character, strengthening religious identity, improving the quality of Islamic religious education, and contributing to the formation of a moral society.